Contribution of outgrowth endothelial cells from human peripheral blood on in vivo vascularization of bone tissue engineered constructs based on starch polycaprolactone scaffolds - Fuchs, Sabine (2009)
In the present study we assessed the potential of human outgrowth endothelial cells (OEC), a subpopulation within endothelial progenitor cell cultures, to support the vascularization of a complex tissue engineered construct for bone. OEC cultured on starch polycaprolactone fiber meshes (SPCL) in monoculture retained their endothelial functionality and responded to angiogenic stimulation by VEGF (vascular endothelial growth factor) in fibrin gel-assays in vitro. Co-culture of OEC with human primary osteoblasts (pOB) on SPCL, induced an angiogenic activation of OEC towards microvessel-like structures achieved without additional supplementation with angiogenic growth factors. Effects of co-cultures with pOB on the vascularization process by OEC in vivo were tested by subcutaneous implantation of Matrigel! plugs containing both, OEC and pOB, and resulted in OEC-derived blood vessels integrated into the host tissue and anastomosed to the vascular supply. In addition, morphometric analysis of the vascularization process by OEC indicated a better performance of OEC in the co-cultures with primary osteoblasts compared to monocultures of OEC. The contribution of OEC to vascular structures and the beneficial effect of the co-culture with primary human osteoblasts on the vascularization in vivo was additionally proven by subcutaneous implantation of pre-cellularized and pre-cultured SPCL constructs. OEC contributed to the vascular structures, by generating autogenic vessels or by incorporation into chimeric vessels consisting of both, human and mouse endothelial cells. The current data highlight the vasculogenic potential of OEC for bone tissue engineering applications and indicate a beneficial influence of constructs including both osteoblasts and endothelial cells for vascularization strategies.